Plant-soil-water interactions: Implications from U-Th-Ra isotope analysis in soils, soil solutions and vegetation (Strengbach CZO, France). (15th August 2019) - Chabaux, François; Stille, Peter; Prunier, Jonathan; Gangloff, Sophie; Lemarchand, Damien; Morvan, Gilles; Négrel, Justine; Pelt, Eric; Pierret, Marie-Claire; Rihs, Sophie; Schmitt, Anne-Désirée; Trémolières, Michèle; et al.
Abstract: This study presents U-Th-Ra isotope data for soils, soil grain size fractions, soil solutions, throughfall, rainwater and tree samples from two experimental plots under spruce and beech trees, in the Strengbach catchment (France) that highlight the importance of the 238 U- 234 U- 230 Th- 226 Ra nuclides and the ( 230 Th/ 232 Th) for the tracing of biogeochemical cycles in the plant-soil-water system of the critical zone (CZ). The results underscore the very contrasting impact of trees on the U-Th and Ra (Ba) budgets in forest ecosystems with Ra-Ba being strongly and U-Th very little cycled by vegetation, leading to high ( 226 Ra/ 230 Th) and ( 226 Ra/ 238 U) in trees. Thorium-Ra(Ba) fractionations in soil solutions and soils are therefore strongly influenced by tree uptake and litter decay but U-Th fractionations are little influenced. Compared to other classical isotope systems such as Sr or Nd that are routinely used in the study of the CZ and significantly affected by vegetation cycling, U-Th isotopes are probably among the few tracers to be specific tracers of water-rock interactions in the CZ. The Th activity ratios of soil minerals, especially of minor and secondary mineral phases, show a large range of variation, from 0.7 to 5 in the Strengabch case. These different characteristics give Th activity ratio an important role for tracing the sources of chemical fluxes in soils, soil solutions and vegetation that is currently under-exploited. The Strengbach study illustrates the utility of this approach and the methodology is further strengthened by the combination of U, Th activity ratios and Sr isotope ratios, which also provides additional constraints on the weathering processes affecting the Strengbach bedrocks and the nature of the reservoirs involved in the plant-soil-water transfers. The results emphasize that minor mineral phases such as zircon, sulfate and phosphate are important sources of the U-Th fluxes circulating in soil solutions and significantly control the U and Th budget of the Strengbach soil samples and their Th activity ratios. Furthermore, the comparison of the U-Th-Sr isotopic characteristics of soil solutions and soil grain size fractions allows the recognition of two stages of weathering of the bedrock i.e. 1- dissolution of the primary minerals and formation of the secondary ones in the deep soil horizons, and 2- dissolution of both primary and secondary minerals mainly from the finest soil grain size fractions in the nearest surface soil horizons. The latter might be related to recent modifications of the weathering processes in the catchment, stronger and older under the spruce than the beech plot. We propose that degree of weathering modification is related to the nature of tree cover because spruce plantations have caused an increase of soil acidity and hence of weathering intensity of some minerals and likely also of Ca leaching from the Ca-poor Strengbach soils over the past decades. The U-Th-Sr results of this study also point to the occurrence of isotopically different reservoirs of these elements for trees and gravity soil solutions collected by lysimetric plates. This further suggests that for the Strengbach watershed the gravity soil solutions cannot be the main tree nutrient reservoir.